2008
DOI: 10.1017/s1481803500009970
|View full text |Cite
|
Sign up to set email alerts
|

Consultation outcomes in the emergency department: exploring rates and complexity

Abstract: Objective: Consultation is a common and important aspect of emergency department (ED) care. We prospectively examined the consultation rates, the admission rates of consulted patients, the emergency physician (EP) disposition prediction of consulted patients and the difficult consultations rates in 2 tertiary care hospitals. Methods: Attending EPs recorded consultations during 5 randomly selected shifts over an 8-week period using standardized forms. Subsequent computer outcome data were extracted for each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 25 publications
(21 reference statements)
1
60
0
2
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Research has explored nonemergent consultations by family medicine physicians 3,4 and the attitudes of consultants during telephone-only consults. 5 In the research on urgent or emergent consultations, [8][9][10][11][12][13][14][15] most studies sought to define and quantify the emergency department (ED) consultation process. [8][9][10][11][12][13] With the advent of the ACGME core competencies and Milestone Project, 16 the teaching and learning of interpersonal and teamwork skills are increasingly highlighted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] Research has explored nonemergent consultations by family medicine physicians 3,4 and the attitudes of consultants during telephone-only consults. 5 In the research on urgent or emergent consultations, [8][9][10][11][12][13][14][15] most studies sought to define and quantify the emergency department (ED) consultation process. [8][9][10][11][12][13] With the advent of the ACGME core competencies and Milestone Project, 16 the teaching and learning of interpersonal and teamwork skills are increasingly highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the research on urgent or emergent consultations, [8][9][10][11][12][13][14][15] most studies sought to define and quantify the emergency department (ED) consultation process. [8][9][10][11][12][13] With the advent of the ACGME core competencies and Milestone Project, 16 the teaching and learning of interpersonal and teamwork skills are increasingly highlighted. To our knowledge this is the first study that has explored interpersonal factors that may influence resident communication during the referral-consultation process within the context of the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of hospitalizations for those patients receiving specialist consultations is highly variable. Cortazzo et al (12) reported that 87% of all consulted patients were admitted, and Woods et al (13) reported that a proportion of 54% were admitted. Curry and Wang (14) reported an admission rate of 68% for the highest acuity site and 64% for the lowest acuity site.…”
Section: Discussionmentioning
confidence: 99%
“…Consultations with inpatient colleagues are used for approximately one-third of patients seen in highvolume, urban tertiary care emergency departments (EDs) in Canada. [1][2][3] In the consultation process, emergency physicians contact specialty services to assist in a patient's care. Requests for consultation are made for different reasons, including hospital admission, treatment or procedure (performed by the consulting service), opinion only, and outpatient referrals.…”
Section: Ré Sumémentioning
confidence: 99%
“…[6][7][8][9][10] Some of the problems identified by emergency physicians include the accessibility and availability of consultants, interactions with consultants, and the disposition decision process. 2,3 Despite their importance, little is known about the causes of consultation delays and the metrics required to measure them.…”
Section: Ré Sumémentioning
confidence: 99%